Battling Esophageal Cancer in The Elderly: A Retrospecive Audit from a Tertiary Cancer Cente in South India - Vedagiri, Gautam Vydia; M, Arun Kumar; K, Ramanaiah; Radhakrisnan, Venkataraman; Krishnamoorthy, Aravind; M N, Arun Kumar; John, Alexander (Asian Pacific Journal of Cancer Nursing, 2025)
Introduction: Esophageal cancer (EC) is a leading malignancy in elderly patients, often diagnosed at an advanced stage due to late presentation. Treatment strategies, including surgery, chemoradiotherapy (CRT), and radiotherapy (RT), must be tailored to this population considering comorbidities and treatment tolerability. This study aims to evaluate treatment outcomes in elderly EC patients and compare findings with global literature. Materials and Methods: A retrospective analysis was conducted on 27 elderly patients diagnosed with EC. Data on patient demographics, tumor histology, treatment modalities, survival duration, and complications were collected from institutional medical records. Statistical analysis included Kaplan-Meier survival estimation and log-rank tests for survival comparison. Findings were compared with existing literature to assess treatment effectiveness and patient outcomes. Results: The mean patient age was 74 years (range: 70-83), with a predominance of male patients (70%). Squamous cell carcinoma (SCC) was the most common histological type (59%). Curative treatment was administered in 59% of patients, while 41% received palliative care. Definitive RT was the most frequently used treatment modality (55%), followed by CRT (30%) and surgery (15%). Kaplan-Meier analysis revealed a median survival of 14 months, with significantly improved survival in curative treatment groups compared to palliative care (p<0.05, log-rank test). Conclusion: Elderly EC patients present unique challenges requiring individualized treatment approaches. This study reinforces the role of definitive CRT as a viable treatment modality, though personalized treatment selection remains essential. Future research should focus on optimizing therapeutic strategies through predictive biomarkers and individualized patient assessments.